Agency Cost, Ukuran Perusahaan, dan Tax Avoidance Terhadap Nilai Perusahaan Dengan Transparansi Informasi sebagai Variabel Moderasi - Fadlillah, Fanny; Maryanti, Eny (Politeknik Ganesha Medan, 2024)
Company value is the price reflected in the expectations and perceptions of share sellers and buyers regarding company performance. It reflects how shareholders view a company's profit potential, known as enterprise value. When the share price of a company is high, it indicates that shareholders expect good performance from the company, which has the potential to provide profits for them. This research aims to evaluate the role of information transparency in moderating the relationship between agency costs, company size, and tax avoidance on company value. This research uses quantitative methods with a sample consisting of 63 mining companies selected through purposive sampling techniques. The research population consists of mining companies listed on the Indonesia Stock Exchange during 2019-2021. The research results show that agency costs and company size have a significant influence on company value, while tax avoidance does not have a significant influence on company value. Information transparency as a moderating variable moderates the relationship between agency costs and firm value. However, information transparency does not moderate the relationship between company size and tax avoidance on company value. Therefore, investors are advised to consider the current effective tax rate of the company when making investments, as a high CETR value may indicate tax avoidance practices, potentially affecting investment returns.